Different predictive value for short-term all-cause mortality with commonly used biomarkers regarding the cause of pulmonary embolism - Jovanović, Ljiljana; Subota, Vesna; Stavrić, Milena; Džudović, Boris; Subotić, Bojana; Novčić, Nataša; Mirić, Milica; Matijašević, Jovan; Nikolić, Maja; Miloradović, Vladimir; Salinger, Sonja; Marković Nikolić, Nataša; et al. (Vojnosanitetski pregled, 2021)
Background/Aim. The evaluation of blood levels of cardiac troponin I (cTnI), D-dimer, B-type natriuretic peptide (BNP), and C-reactive protein (CRP) on admission and during the treatment of pulmonary embolism (PE) are the part of routine diagnostic process and estimation of mortality risk. The aim of this study was to evaluate the predictive value of these biomarkers on admission for all-cause 30-day mortality in consecutive PE patients regarding whether they classified as spontaneous, transiently provoked, or permanently provoked PE. Methods. This retrospective analysis was gained from the data of 590 PE patients from the Serbian University Multicenter Pulmonary Embolism Registry (SUPER). Patients had at least one of these biomarkers (BNP, CRP, cTnI, and D-dimer) measured during the first 24 hours upon admission. Results. Receiver operating characteristic (ROC) curve analyses demonstrated that BNP had the highest prognostic accuracy for 30-day mortality in patients (n = 219) who had data for all examined biomarkers. BNP provided an AUC of 0.785 (p
Keywords: pulmonary embolism; biological factors; mortality; risk assessment; natriuretic peptides; troponin I; c-reactive protein